2005
DOI: 10.1071/en05018
|View full text |Cite
|
Sign up to set email alerts
|

Caudal Fin Mercury as a Non-Lethal Predictor of Fish-Muscle Mercury

Abstract: Environmental Context. Surveys to assess the body burden of mercury in fish to support research or contamination advisory programs typically involve capturing and killing fish and analyzing muscle tissue for mercury. Lethal sampling may not be feasible in protected waters or in studies involving threatened or endangered species. We analyzed tail fin samples of two fish species for total mercury and compared results with muscle-tissue mercury and concluded that fin-Hg can be used as a predictor of muscle-Hg. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 12 publications
(15 reference statements)
1
16
1
1
Order By: Relevance
“…The relationships between fin and muscle tissue Hg concentration in the present study, as determined from R 2 -values, are similar to those previously reported (Baker et al 2002; Gremillion et al 2005; Lake et al 2006; Rolfhus et al 2008; Ryba et al 2008). Previous studies that examined the fin clips of freshwater fishes as a surrogate measurement for muscle tissue Hg yielded R 2 -values between 0.62 and 0.85 (mean = 0.74) (Table 3).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The relationships between fin and muscle tissue Hg concentration in the present study, as determined from R 2 -values, are similar to those previously reported (Baker et al 2002; Gremillion et al 2005; Lake et al 2006; Rolfhus et al 2008; Ryba et al 2008). Previous studies that examined the fin clips of freshwater fishes as a surrogate measurement for muscle tissue Hg yielded R 2 -values between 0.62 and 0.85 (mean = 0.74) (Table 3).…”
Section: Resultssupporting
confidence: 92%
“…Nonlethal sampling techniques as predicators of muscle tissue Hg concentration have been examined in freshwater fishes, including the analysis of muscle biopsies (Baker et al 2004; Schmitt and Brumbaugh 2007), blood (Schmitt and Brumbaugh 2007), anal, caudal, and pelvic fin clips (Gremillion et al 2005; Rolfhus et al 2008) and scales (Lake et al 2006). The use of muscle tissue biopsies and blood samples of freshwater fishes provided a reliable alternative to traditional whole-fish methods; however, these sampling techniques may be invasive and potentially more difficult, expensive, and time-consuming to collect (Baker et al 2004; Schmitt and Brumbaugh 2007).…”
mentioning
confidence: 99%
“…Studies conducted elsewhere have demonstrated the utility of muscle biopsy sampling as an alternative to sampling fillets or whole fish for Hg monitoring (Baker et al 2004;Cizdziel et al 2002aCizdziel et al , 2003Peterson et al 2002Peterson et al , 2005Uthe 1971) and selenium (Hamilton et al 2004;Waddell and May 1995) and for obtaining samples for genetic analyses (Crawford et al 1977;Leitner and Isely 1994). The analysis of scales (Lake et al 2006) and caudal fin tissue (Gremillion et al 2005) have also been evaluated for Hg. Blood sampling represents a feasible alternative for monitoring Hg in wildlife (Franson et al 1999) and humans (Hightower and Moore 2003) and for lead and cadmium in fish (Brumbaugh et al 2005), but it has received only limited investigation for Hg in fish (e.g., Cizdziel et al 2003).…”
mentioning
confidence: 99%
“…In general, the results of such studies tend to support the use of fin analysis for both heavy metal and stable isotope analysis (e.g., Gremillion et al 2005; Hg concentration in muscle (ln(mg/kg)) Hg concentration in scales (ln(mg/kg)) -3. Fig.…”
Section: Relationship Between Muscle and Scale Concentrationsmentioning
confidence: 89%
“…Sauer and Watabe 1989;Farrell et al 2000;Gremillion et al 2005;Lake et al 2006;Rolfhus et al 2008;Ryba et al 2008;Červenka et al 2011). Scales, in particular, are convenient as they can be taken repeatedly from the same fish and are chemically stable for a long time, allowing analysis of archived material.…”
Section: Introductionmentioning
confidence: 99%